Edukasi dan Penerapan Lubang Resapan Biopori untuk Mengurangi Genangan di Desa Suwangi Timur Kecamatan Sakra - Budianto, Muh Bagus; I Wayan Yasa; Humairo Saidah; IDG Jaya Negara; Ery Setiawan; Dewandha Mas Agastya (Universitas Mataram, 2024)
Suwangi Timur Village is one of the villages in Sakra District which is passed by the provincial road, namely Jalan Soekarno Hatta, which has many important facilities and infrastructure. The problem that is often faced is that there is often puddles at several points along the road. This condition not only interferes with passing vehicles but also causes discomfort for the people living around it. The community service activity is intended to reduce puddles by using an environmentally friendly method, namely by making biopore infiltration holes (BIH). This method can not only reduce puddles but also serve as an effort to conserve land and water. The community is very enthusiastic about participating in this activity from socialization, making to implementing BIH. In this activity, 10 BIH have been installed.